DEVELOPING STUDENTS’ MATHEMATICAL UNDERSTANDING USING GEOGEBRA SOFTWARE - Zikra Hayati; Khairatul Ulya (Jurnal Ilmiah Didaktika, 2022)
Technology is an essential reference in all aspects. Technology provides significant changes in education part, especially in learning mathematics. Technology has an impact on the innovation space in mathematics learning, the problems so far tend to be less attractive, the environment is boring and very tied to reading materials, which results in students still not being able to develop their mathematical thinking process optimally, namely students' mathematical understanding is still low. Students' mathematical understanding is one of the most important capabilities that students should have to solve various problems, both mathematical problems for instance problems related to concepts, operations, principles, and in daily life. So that innovation in learning with the influence of learning technology is important to apply. The aim of this study was to develop students' conceptual understanding of transformation geometry using Geogebra software. This study used exploratory mixed methods designs that aimed to describe students' understanding of mathematics by learning using Geogebra software. The results of the study indicate that usage Geogebra software can develop students' understanding of mathematical concepts in the transformation geometry, and assisted teachers create an interesting and fun learning process, teachers find the right procedures in using applications such as the use of different software and techniques in learning mathematics, making it easier for students to understand the abstract material of transformation geometry. The results of this study are focused on test analysis, namely exploring students' mathematical understanding, data can also be obtained from interview techniques that explore test answers, in the form of 2 problems related to transformation geometry. The results of the study indicate that are 5 criteria that have met the students' understanding of mathematics from 7 indicators.